2014
DOI: 10.1063/1.4866177
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of side chain and excess energy on the charge photogeneration dynamics of low-bandgap copolymer-fullerene blends

Abstract: Primary charge photogeneration dynamics in neat and fullerene-blended films of a pair of alternating benzo[1,2-b:4,5-b(')]dithiophene (BDT) and thieno[3,4-b]thiophene (TT) copolymers are comparatively studied by using near-infrared, time-resolved absorption (TA) spectroscopy under low excitation photon fluence. PBDTTT-E and PBDTTT-C, differed merely in the respective TT-substituents of ester (-E) and carbonyl (-C), show distinctly different charge photogeneration dynamics. The pair of neat PBDTTT films show ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…As for the neat PBDTTT-E layer, it exhibits a main absorption band in the wavelength range of 500–800 nm with two absorption peaks at 680 and 626 nm. The former absorption peak is often referred to as the vibronic progression of the electronic state (0′-0), whereas the latter peak is considered as the (1′-0) vibronic absorption of electronic transition, and they both are in relation to the aggregation state of co-polymers ( Clark et al, 2009 ; Hu et al, 2014 ; Huo et al, 2014 ; Fauvell et al, 2016 ). Herein, the relative absorption intensity of the 626 nm peak of the neat PTB7 film ( A 1´-0 / A 0´-0 ) is slightly enhanced comparing with that of the PBDTTT-E film, suggesting that the fluorine substituent can influence the co-planar conformation and optical absorption of the polymer ( Leclerc et al, 1993 ; Huo et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…As for the neat PBDTTT-E layer, it exhibits a main absorption band in the wavelength range of 500–800 nm with two absorption peaks at 680 and 626 nm. The former absorption peak is often referred to as the vibronic progression of the electronic state (0′-0), whereas the latter peak is considered as the (1′-0) vibronic absorption of electronic transition, and they both are in relation to the aggregation state of co-polymers ( Clark et al, 2009 ; Hu et al, 2014 ; Huo et al, 2014 ; Fauvell et al, 2016 ). Herein, the relative absorption intensity of the 626 nm peak of the neat PTB7 film ( A 1´-0 / A 0´-0 ) is slightly enhanced comparing with that of the PBDTTT-E film, suggesting that the fluorine substituent can influence the co-planar conformation and optical absorption of the polymer ( Leclerc et al, 1993 ; Huo et al, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…After single dissolution, the polymer and fullerene are evenly distributed in the solvent. Only some polymers, however, are unfolded and kinked polymer chains remain in solution, which has been observed in PBDTTT systems [28,29]. The unfolded polymer configuration will remain in polymer:fullerene films after solvent volatilization.…”
Section: Photovoltaic Behaviors Of Ptb7:pc71bm Devicesmentioning
confidence: 99%
“…The unfolded polymer configuration will remain in polymer:fullerene films after solvent volatilization. Moreover, it has been found that the ratio of kinked conformation depends on the solvents [28,29]. When the polymer:fullerene film is redissolved in another solvent, the configuration of original kinked polymers can be further extended to the unfolded mode by solvent-induced regulation.…”
Section: Photovoltaic Behaviors Of Ptb7:pc71bm Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thin-film organic solar cells have attracted a lot of interests because organic cells are expected as replacements for silicon solar cells and inorganic electronic materials owing to higher processability and lower-cost devices. Conjugated polymers have extensively been used in thin-film organic solar cells, and they act as electron donors and hole transporters in bulk heterojunction (BHJ) films. Homopolymers, poly­(3-hexylthiophene) (P3HT) and poly­[2-methoxy-5-(2′-ethylhexyloxy)- p -phenylene vinylene] (MEH-PPV), , have rigorously been studied as electron donors in solar cells.…”
Section: Introductionmentioning
confidence: 99%